2004
DOI: 10.1128/cdli.11.5.862-867.2004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Eight Commercial Enzyme Immunoassay Tests for Detection of Antibodies to Mycoplasma pneumoniae in Human Serum

Abstract: Mycoplasma pneumoniae is an important etiologic agent of primary atypical pneumonia in children and adults. The diagnosis of M. pneumoniae infection is commonly confirmed through serologic testing. In this study, we used paired sera from 51 patients (all with confirmed M. pneumoniae infection and positive complement fixation [CF] titers) to compare the results of eight enzyme immunoassays (EIAs) available commercially in the United States. We compared two single-use EIAs and six plate-type EIAs. Results from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 20 publications
4
49
0
Order By: Relevance
“…Many require collection of both acute-and convalescent-phase samples to identify a 4-fold increase in titer suggestive of an active infection [6]. Although serologic tests may provide important retrospective information, the impracticality of obtaining the followup sample limits their use when rapid confirmation of etiology is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many require collection of both acute-and convalescent-phase samples to identify a 4-fold increase in titer suggestive of an active infection [6]. Although serologic tests may provide important retrospective information, the impracticality of obtaining the followup sample limits their use when rapid confirmation of etiology is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Complement fixation testing lacks sensitivity and specificity [5]. Commercially available serologic test kits for detection of antibodies to M. pneumoniae possess inherent limitations of specificity and sensitivity and, more importantly, depend on patient compliance with the timely acquisition of acute-and convalescent-phase serum samples for accurate interpretation [6]. Molecular-based assays, such as real-time PCR, have recently been shown to aid in the rapid identification of outbreaks of M. pneumoniae infection and provide greater sensitivity than do traditional methods [7][8][9][10].…”
mentioning
confidence: 99%
“…Several commercial tests utilizing passive agglutination, indirect immunofluorescence and immunoenzymatic assays are available and widely used for the detection of antibodies specific to M. pneumoniae in human sera. The complement fixation test, being as it is unspecific and insensitive, is no longer accepted [18]. However, several factors i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IgM antibodies may not be present if the serum sample is obtained too early in the infection. Moreover, an IgM response may be either minimal or undetectable when adults are infected and during re-infection [16,18]. Thus, a negative result of IgM evaluation does not exclude current infection, especially in patients over the age of 45 years.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that only 14 of 27 (52%) acute-phase sera tested positive by various IgM assays, but this number rose to 39 (88%) when convalescent sera were tested [ 30 ]. The percentage of persons with acute infection that demonstrate a positive IgG response in the acute phase was less than 50% in the same study, but when convalescent sera were tested, the IgG-positive specimens rose to 82% [ 30 ]. Thus, defi nitive diagnosis requires seroconversion in paired sera obtained 2 to 4 weeks apart and assayed at the same time.…”
Section: Serologymentioning
confidence: 90%